Functional venomics of the Big-4 snakes of Pakistan. (May 2020) - Hashmi, Syeda U.; Alvi, Areej; Munir, Iqra; Perveen, Mehvish; Fazal, Amaila; Jackson, Timothy N.W.; Ali, Syed A.
Abstract: In South Asia, the "Big-4" venomous snakes Naja naja, Bungarus caeruleus, Daboia russelii, and Echis carinatus are so-called because they are the most medically important snakes in the region. Antivenom is the only effective treatment option for snakebite envenoming but antivenom is not produced domestically in Pakistan making the country reliant on polyvalent products imported from India and Saudi Arabia. The present study investigated the toxin composition and activity of the venoms of Pakistani specimens by means of proteomic and physio/pharmacological experiments. To evaluate the composition of venoms, 1D/2D-PAGE of crude venoms and RP-HPLC followed by SDS-PAGE were performed. Enzymatic, hemolytic, coagulant and platelet aggregating activities of crude venoms were assayed and were concordant with expectations based on the abundance of protein species in each. Neutralization assays were performed using Bharat polyvalent antivenom (BPAV), a product raised against venoms from Big-4 specimens from southern India. BPAV exhibited cross-reactivity against the Pakistani venoms, however, neutralization of clinically relevant activities was variable and rarely complete. Cumulatively, the presented data not only highlight geographical variations present in the venoms of the Big-4 snakes of South Asia, but also demonstrate the neutralization potential of Indian polyvalent against the venom of Pakistani specimens. Given the partial neutralization observed, it is clear that whilst BPAV is a life-saving product in Pakistan, in future it is hoped that a region-specific product might be manufactured domestically, using venoms of local snakes in the immunising mixture. Graphical abstract: Image 1 Highlights: The "Big-4" snakes are responsible for the majority of snakebite fatalities in South Asia. Pakistani Big-4 snake venoms differ in toxin composition and activity. Bharat polyvalent antivenom exhibited cross-reactivity against the Pakistani Big-4 venoms. Neutralization of toxin activities was found to be variable. Immunorecognition of BPAV was greater for viperid snake venoms.